Enhancing object clarity in single channel night vision images using deep reinforcement learning - Hossain, Adil; Robbani, Mohammad Elham; Sazid, Md. Riaz Ul Haque; Siam, Sk. Shahiduzzaman; Abtahee, Wasiu (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.